Mapping Cognitive Load and Thinking Zones in Understanding Function Limits - Oktaviyanthi, Rina; Agus, Ria Noviana (Department of Mathematics Education Program IPI Garut, 2025)
Penelitian ini merespons terbatasnya kajian yang memetakan pola berpikir siswa berdasarkan beban dan zona kognitif dalam memahami limit fungsi secara grafis. Dengan menggunakan teori beban kognitif dan klasifikasi zona (risiko, tantangan, optimal), enam mahasiswa dipilih secara purposif dalam studi kasus kualitatif untuk mewakili variasi kemampuan. Data berupa respons tertulis dan think-aloud dianalisis untuk menelusuri transisi zona kognitif. Hasil menunjukkan pola kognitif yang beragam, dari miskonsepsi hingga integrasi konseptual. Beban tinggi dapat dikelola melalui regulasi diri, sedangkan beban rendah tetap berisiko jika struktur pemahaman belum berkembang. Studi ini menekankan pentingnya instruksi adaptif berdasarkan profil kognitif mahasiswa dan menawarkan kerangka zona berpikir untuk mendukung pembelajaran matematika yang personal. This study addresses the limited research mapping students’ thinking patterns through cognitive load and cognitive zones in understanding function limits graphically. Using Cognitive Load Theory and the classification of risk, challenge, and optimal zones, six first-year mathematics education students were purposively selected in a qualitative case study to represent varying academic abilities. Data from written responses and think-aloud protocols were analyzed to trace zone transitions. Findings showed diverse cognitive patterns, from misconceptions to successful conceptual integration. High cognitive load was manageable through self-regulation, while low load still poses risks if the understanding structure is undeveloped. The study highlights the importance of adaptive instruction aligned with students’ cognitive profiles and offers a thinking zone framework to support personalized mathematics learning.